2012
DOI: 10.1590/s0100-736x2012000500010
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ivermectin-resistant gastrointestinal nematodes in feedlot cattle in Argentina

Abstract: The aim was to evaluate for 75 days the impact on production of the remaining burden of ivermectin (IVM)-resistant parasites in naturally infected feedlot calves. The herds came from tick-infested areas of cattle breeding where the systematic use of IVM to control tick increases the gastrointestinal parasites resistant to this drug. This investigation was carried out in two commercial feedlots in Buenos Aires province. In feedlot A, two groups of 35 animal each received IVM 1% and the other received ricobendaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
(20 reference statements)
0
5
1
1
Order By: Relevance
“…has already been reported (Herlich, 1965;Keith, 1967;Louvandini et al, 2009;Stromberg et al, 2011) as well as the impact of this genus combined with Haemonchus sp. in feedlot calves (Fazzio et al, 2011(Fazzio et al, , 2012. In this trial, the prevailing parasite genus in PT fecal cultures was Cooperia, while Haemonchus was present in smaller amounts.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…has already been reported (Herlich, 1965;Keith, 1967;Louvandini et al, 2009;Stromberg et al, 2011) as well as the impact of this genus combined with Haemonchus sp. in feedlot calves (Fazzio et al, 2011(Fazzio et al, , 2012. In this trial, the prevailing parasite genus in PT fecal cultures was Cooperia, while Haemonchus was present in smaller amounts.…”
Section: Discussionmentioning
confidence: 65%
“…In Argentina, more than 1.100.000 animals a year are fattened in feedlots (Rossanigo et al, 2010). Weight loss due to lack of drug efficacy as a result of AR could be substantial in these production systems (Fazzio et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Low efficiency at a lowest dosage of ivermectin in this study was reported by Fazzio et al (2012) in Argentina, who observed an RFEC rate of 28.4%, 22 days after the treatment of calves, while Soutello et al (2010) reported that the highest RFEC (72.2%) was observed 3 days after treatment and for 28 days thereafter, which was evaluated after administration of 1% ivermectin. On the Santa Catarina plateau, 18% of the cattle had an efficacy greater than 95% and 5% and less than 14% (SOUZA et al, 2008).…”
Section: Introductionmentioning
confidence: 39%
“…El hecho de que las lactonas macrocíclicas eran los AH de preferencia en las granjas estudiadas podría crear una mayor presión para la selección de NG resistentes. Varios reportes ya existen de la resistencia a la ivermectina en regiones tan diversos como el norte de California, Estados Unidos (32) ; Buenos Aires, Argentina (33) ; y en São Paulo y Minas Gerais, Brasil (30,34) . Esto resalta la importancia de evaluar el perfil de susceptibilidad de un AH en cada región o hato para asegurar que va a ejercer un control efectivo de los NG (33) .…”
Section: Control De La Helmintiasisunclassified